A note on nano-photovoltaic panels emergence in energy market - Filipe, J. A.; Neto, J. C.; Ferreira, M. A. M. (International Journal of Latest Trends in Finance and Economics Sciences, 2015)
Nanotechnology may work as a powerful weapon to be used for creating competitive advantages in the energy market. Through the use of photovoltaic nano-panels, which may reduce considerably production costs and simultaneously meet socioenvironmental requirements demanded by law. It is a way to produce clean energy in innovative terms. Moreover, today the adoption of nanotechnology in energy production can in turn make this kind of energy quite interesting through time. Nanotechnology may be responsible for considerable economic and environmental gains.